Multiomic features associated with mucosal healing and inflammation in paediatric Crohn's disease - Taylor,H; Serrano-Contreras,JI; McDonald,JAK; Epstein,J; Fell,JM; Seoane,RC; Li,JV; Marchesi,JR; Hart,AL (Alimentary Pharmacology and Therapeutics, 2020)
BACKGROUND: The gastrointestinal microbiota has an important role in mucosal immune homoeostasis and may contribute to maintaining mucosal healing in Crohn's disease (CD). AIM: To identify changes in the microbiota, metabolome and protease activity associated with mucosal healing in established paediatric CD. METHODS: Twenty-five participants aged 3-18 years with CD, disease duration of over 6 months, and maintenance treatment with biological therapy were recruited. They were divided into a low calprotectin group (faecal calprotectin <100 μg/g, "mucosal healing," n = 11), and a high calprotectin group (faecal calprotectin >100 μg/g, "mucosal inflammation," n = 11). 16S gene-based metataxonomics, 1 H-NMR spectroscopy-based metabolic profiling and protease activity assays were performed on stool samples. RESULTS: Relative abundance of Dialister species was six times greater in the low calprotectin group (q = 0.00999). Alpha and beta diversity, total protease activity and inferred metagenomic profiles did not differ between groups. Pentanoate (valerate) and lysine were principal discriminators in a machine-learning model which differentiated high and low calprotectin samples using NMR spectra (R2 0.87, Q2 0.41). Mean relative concentration of pentanoate was 1.35-times greater in the low calprotectin group (95% CI 1.03-1.68, P = 0.036) and was positively correlated with Dialister. Mean relative concentration of lysine was 1.54-times greater in the high calprotectin group (95% CI 1.05-2.03, P = 0.028). CONCLUSIONS: This multiomic study identified an increase in Dialister species and pentanoate, and a decrease in lysine, in patients with "mucosal healing." It supports further investigation of these as potential novel therapeutic targets in CD.